The issues and complexities of establishing methodologies to differentiate between vertical and horizontal impact mechanisms in the analysis of skeletal trauma: An introductory femoral test. (June 2021) - Dempsey, Nicholas; Bassed, Richard; Blau, Soren
Abstract: Understanding skeletal trauma characteristics is fundamental for the examination and interpretation of blunt force trauma (BFT). BFT is the most complex type of trauma to interpret based on the analysis of skeletal fractures alone, with comminuted fractures presenting additional complications to assess and interpret. Considerable variation exists within each type of BFT injury dependent on direction, magnitude of force, plus a myriad of biological/environmental factors. Given the complex processes governing the nature of BFT skeletal injuries determining whether differences between impact mechanisms and skeletal trauma can be quantified requires investigation. Aim: this study aims to determine the feasibility of quantifying outcomes between two separate loading conditions by using a formula created from transformed variables recorded from specific trauma cases involving BFT to the femur. Methodology: Displacement, comminution, and femoral midshaft area data were recorded from full body postmortem computed tomography scans of 103 individuals (males, mean age 42.5, and females, mean age 48.9) where cause of death was the result of rapid horizontal deceleration impact events (pedestrian motor vehicular accidents, n = 59) and vertical (>3-metre falls, n = 44). These measurements were standardised and transformed into a continuous variable. Independent t -tests, binary logistic regression and K Nearest- Neighbours (KNN) were used to analyse the data. Results: The standardised values showed mean group differences between falls (9.62) and pedestrian motor vehicular impacts (pedestrian MVAs) (9.53), however, these results were not statistically significant. The results indicate that similarities in variance between types of trauma outcomes and impact mechanisms demonstrate low equivalency (samples have limited differences), and the overall limitations in relying on using single elements to explain complex skeletal trauma outcomes. Highlights: Impact mechanisms can be difficult to interpret on the basis of skeletal fracture analysis alone. Catastrophic skeletal trauma outcomes can obfuscate the potential mechanisms of impact. Skeletal trauma outcomes need to be analysed as a continuum, and not as discrete categories. Extrapolating the results of experimental research and applying them to forensic cases is problematic.